Investment by Ethiopian Government Universities to Run Community-based Breeding Programs (CBBPs) in Nearby Villages as part of their Outreach Program - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
CBBP is a proven innovation that has been tested over the years through the engagement of multiple stakeholders. However, the pilots have not scaled to the extent they wished. The actors of CBBP were research institutes, extension and NGOs. To bring about impact at scale, various partners need to join hands to disseminate the innovation to a wider area and reach more beneficiaries. Engaging multiple stakeholders having a shared mandate is important to scale up the proven technology. Universites, although they have a tremendous role in scaling of innovations as part of their outreach program, their involvement was minimal. Initiating CBBPs in nearby villages ensures the synergy of research, education and community service of the Universities. With this rationale, we undertook awareness creation at different levels of the University staff and we were able to convince them to allocate resources to benefit from CBBP to synergize the triple mandates of the Universities. The Universities have, therefore, allocated a budget by considering CBBP as a flagship project covering over five years. The budget allocation passed through a rigorous review process under the community services program. The budget allocation is meant for enumerator contractual payments, material purchases to run baseline information, medicaments, supervision cost and capacity building at each stage. There is a consistent increase of participating universities in running CBBP, and benefiting from the experience. As a result, more than 16 Universities have allocated a budget (40,337,656 Birr (706,108 USD)) to run 42 CBBPs.